Dual Synchronization of Fractional-Order Chaotic Systems via a Linear Controller - Jian Xiao; Zhen-zhen Ma; Ye-hong Yang (The Scientific World Journal)
The problem of the dual synchronization of two different fractional-order chaotic systems is studied. By a linear controller, we realize the dual synchronization of fractional-order chaotic systems. Finally, the proposed method is applied for dual synchronization of Van der Pol-Willis systems and Van der Pol-Duffing systems. The numerical simulation shows the accuracy of the theory.